2018
DOI: 10.1111/aas.13247
|View full text |Cite
|
Sign up to set email alerts
|

Optimal PEEP during one‐lung ventilation with capnothorax: An experimental study

Abstract: Optimal PEEP was 12-18 cm H O and probably relates to capnothorax insufflation pressure. With suboptimal PEEP, ventilation/perfusion mismatch in the ventilated lung and redistribution of blood flow to the nonventilated lung occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Once inflammatory factors are out of balance, they will lead to serious adverse consequences. IL-10 is an anti-inflammatory and immunosuppressive factor that inhibits the release of proinflammatory mediators such as IL-6 and TNF-α[ 20 ]. The results of this study showed that at 4 h after surgery, the measured values of TNF-α and IL-6 in group A were lower than those in group B, and the differences were significant ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Once inflammatory factors are out of balance, they will lead to serious adverse consequences. IL-10 is an anti-inflammatory and immunosuppressive factor that inhibits the release of proinflammatory mediators such as IL-6 and TNF-α[ 20 ]. The results of this study showed that at 4 h after surgery, the measured values of TNF-α and IL-6 in group A were lower than those in group B, and the differences were significant ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…An animal experiment also confirmed the importance of individualized PEEP, in which Reiniush et al obtained the appropriate range of PEEP according to oxygenation, driving pressure and cardiac output. PEEP exceeded this range would cause ventilation/perfusion mismatch of the ventilated lung 111 . The optimal PEEP remains a matter of considerable debate.…”
Section: Explore the Optimal Individualized Peep Valuementioning
confidence: 99%
“…PEEP exceeded this range would cause ventilation/perfusion mismatch of the ventilated lung. 111 The optimal PEEP remains a matter of considerable debate. This uncertainty has fostered various setting approaches.…”
Section: Explore the Optimal Individualized Peep Valuementioning
confidence: 99%
“…Reversal of atelectasis by PEEP improves the oxygenation by decreasing shunt and improves the mechanical properties of the ventilated lung (12). Conversely, use of excessive PEEP might induce lung overdistension and increase regional PVR.…”
Section: Peepmentioning
confidence: 99%